Consumer Risk Perceptions and Attitudes about Beef Food Safety: Implications for Improving Supply Chain Management - Schroeder, Ted C.; Tonsor, Glynn T.; Mintert, James; Pennings, Joost M.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Recent concerns about food safety have been the most disruptive and costly events the Canadian beef industry has ever experienced. At best, food safety scares reduce consumer confidence in beef products. At worst, complete loss of beef market access occurs because of a food safety event. Either scenario, reduced consumer confidence in beef safety or loss of market access, adds considerable stress to the Canadian beef industry as reduced consumer demand causes lower beef and cattle prices. The research conducted for this study revealed numerous strategies that the Canadian beef industry could pursue to enhance product demand.
Keywords: Consumers; Beef; Food safety; Supply chain management; Canada; Brand equity